Efeito da adição de caldo de cana-de-açúcar na dinâmica da população de Escherichia coli e presença de E. Coli shigatoxigênicas durante a codigestão anaeróbia de dejetos bovinos leiteiros - Branco, Paula Maria Pilotto [UNESP] (2018)
The objective of this study was to evaluate the effects of the addition of sugarcane juice on the population dynamics of Escherichia coli and the presence of Shiga-toxigenic E. coli (STEC) during the anaerobic codigestion of dairy cattle manure. For the overall analyses at the end of a hydraulic retention time of 90 days, ten two-liter batch-type biodigesters were divided into two treatment groups: biodigester containing manure and water (MW) and the biodigester containing manure, water and sugarcane juice (MSC). For monitoring the population dynamics and presence of microorganisms, pH, and volatile acidity, tests were carried out every ten days, on 36 smaller-scale batch biodigesters made of one-liter plastic bottles (18 for each treatment). The reductions in E. coli population over time were significant in the MW (60 days) and MSC (20 days) biodigesters. Inactivation of STEC occurred in a shorter period (40 days in MW and <10 days in MSC). Significant differences were obtained between the two treatments, with the pH values being lower, the concentrations of volatile acids (VA) being higher, and the inactivation of E. coli and STEC being faster in the biodigester with sugarcane juice added. The amount of sugarcane juice applied (7%) suggests its suitability for the sanitization of dairy cattle manure for use as a biofertilizer, given the high reduction in the E. coli population and inactivation of STEC.